Network pharmacology and gut microbiota insights: unraveling Shenling Baizhu powder’s role in psoriasis treatment - Tang, Bin; Zheng, Xuwei; Luo, Qianqian; Li, Xiong; Yang, Yujie; Bi, Yang; Chen, Yonggen; Han, Ling; Chen, Haiming; Lu, Chuanjian (Frontiers in Pharmacology, 2024)
Background: Psoriasis, a chronic skin condition characterized by systemic inflammation and altered gut microbiota, has been a target of Traditional Chinese Medicine (TCM) for centuries. Shenling Baizhu Powder (SLBZP), a TCM formulation, holds promise for treating inflammatory diseases, but its specific role in psoriasis and impact on gut microbiota is not fully understood.Objective: This study aims to elucidate the mechanism of SLBZP in treating psoriasis, integrating component analysis, network pharmacology, and experimental validation in mice models.We commenced with a detailed component analysis of SLBZP using liquid chromatograph and mass spectrometer (LC-MS). Network pharmacology analysis was used to predict the potential action targets and pathways of SLBZP in psoriasis. An in vivo experiment was conducted with psoriasis mice models, treated with SLBZP.Therapeutic effects were assessed via symptomatology, histopathology, and immunohistochemical analysis. Gut microbiota composition was analyzed using 16S rRNA gene sequencing.Results: A total of 42 main components and quality markers were identified, primarily from licorice and ginseng, including flavonoids, saponins and other markers. PPI topology analysis showed that TNF, IL-6, IL-1β, TP53 and JUN were the core DEPs.168 signaling pathways including lipid and atherosclerosis, AGE-RAGE signaling pathway, IL-17 signaling pathway and Th17 cell differentiation were enriched by KEGG. SLBZP demonstrated significant therapeutic effects on psoriasis in mice, with alterations in skin pathology and biomarkers. Additionally, notable changes in gut microbiota composition were observed post-treatment, indicating a possible gut-skin axis involvement.Conclusions: This research has pinpointed lipid metabolism as a key pathway in the treatment of psoriasis with SLBZP. It explores how SLBZP's modulation of gut microbiota and lipid metabolism can alleviate psoriasis, suggesting that balancing gut microbiota may reduce inflammation mediators and offer therapeutic benefits. This underscores lipid metabolism modulation as a potential new strategy in psoriasis treatment.